Enhancing learning in the laboratory : Identifying and promoting best practice in the professional development of demonstrators : final report. - Mocerino, Mauro (Australia. Dept of Education, Skills and Employment, 2021)
Laboratory classes are essential components of science and engineering degrees. In response to concerns about quality of instruction in laboratories, a Laboratory Demonstrators Professional Development Program was developed at Curtin University to enhance the teaching skils of laboratory demonstrators. In 2013, this professional development program received an Office of Learning and Teaching Award for programs that enhance learning. The Fellowship program aimed to improve the learning experience of students in laboratories through the enhanced professional skills of demonstrators. Following consultation with national and international scholars in institutions that have established PD programs, a refined professional development program was developed and disseminated across Australia via local facilitators. A series of scoping and planning meetings were held with colleagues in November 2015 to share ideas and scope the possibility of hosting a professional development workshop at their institution the following year. The workshops were designed to be interactive with a high level of "think/write/pair/share" activities. The workshop delivery was designed to model good teaching behaviour and participants were often asked to reflect on the behaviour of the facilitators. The focus of the workshops is on pedagogy with little on local logistics or discipline content. At the completion of the workshop, participants were asked to complete a short evaluation form. A total of 277 survey response forms were received with a gender balance of approximately 50 percent male/female. [Publisher summary, ed]